Serum leptin and neuropeptide Y in patients with cystic fibrosis—A single center study - Galiniak, Sabina; Podgórski, Rafał; Rachel, Marta; Mazur, Artur (Frontiers in Medicine, 2022)
Along with the significant elongation in the average life expectancy of patients with cystic fibrosis (CF), there are still significant discrepancies in the height, weight, and body mass index (BMI) of patients compared to controls without CF. The correlation between hormones that regulate appetite and body fat mass may be an additional factor in weight loss or poor weight gain in CF patients.. Our objective was to estimate serum concentrations of leptin and neuropeptide Y in patients with CF as well as to assess correlations between studied hormones and the clinical parameters of CF. Leptin and neuropeptide Y serum concentrations after an overnight fast were measured using an enzyme-linked immunosorbent assay. All study participants had anthropometric tests and spirometry. In addition, fasting serum lipid profile was also analyzed. Fasting leptin levels in CF were significantly higher in patients with CF patients (13.9±6.9 vs. 6.5± 2.6 ng/mL, p<0.001) compared to controls. There were no differences in leptin concentration between female and male CF participants (15.7±7.8 vs. 12.2±5.6 ng/mL, p=0.13). Leptin was correlated with age (R=0.64, p<0.001), BMI (R=0.65, p<0.001), spirometry results (R=-0.49, p<0.01) and body fat (R=0.5, p<0.05). There were no differences in neuropeptide Y concentration between participants with CF and controls as well as neuropeptide Y was not correlated with any studied parameters. The results of our study suggest that weight loss may be associated with a decreased level of leptin, while reduced pulmonary function in CF may be related to an elevated level of leptin.